Mineral Resource Investigations Of Selected Roadless Areas In Idaho National Forests ? Introduction - Ronald B. Stotelmeyer (The National Institute for Occupational Safety and Health (NIOSH), 1994)
This report summarizes studies of 55 Idaho national forest roadless areas completed by the U.S. Bureau of Mines (USBM) in the period 1966-1992. These roadless areas have been recommended for addition to the National Wilderness Preservation System, proposed as special management areas, or otherwise recommended for study by the U.S. Forest Service or the Idaho congressional delegation. The Bureau of Mines' studies indicate which parts of the roadless areas contain mineral resources. They also show where mining and prospecting are likely to occur in the future, where mineral production has occurred in the past, and where abandoned mine workings (possible hazards) would be encountered. The number of mine and prospect workings found are a measure not only of surface disturbance, but of areas not wilderness in character.